2019
DOI: 10.1186/s13002-019-0305-4
|View full text |Cite
|
Sign up to set email alerts
|

Traditional knowledge and cultural importance of Gardenia erubescens Stapf & Hutch. in Sudanian savanna of Burkina Faso

Abstract: Background Traditional knowledge (TK) on the different uses of under-valued fruit tree species including Gardenia erubescens Stapf & Hutch.—a plant species of least concern (LC) based on International Union for Conservation of Nature (IUCN) classification yet considered threatened due to overharvesting by a National Assessment in addition to 59 other species in Burkina Faso. This study aimed to collect and synthesize information on traditional knowledge and cultural impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 23 publications
0
19
0
3
Order By: Relevance
“…Ouedraogo et al . [ 21 ] reported that relative frequency of citation could also be counted based on FL. This is designed to measure species importance for specific purposes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ouedraogo et al . [ 21 ] reported that relative frequency of citation could also be counted based on FL. This is designed to measure species importance for specific purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Fidelity Level (FL). The relative frequency of citation was calculated using the fidelity level (FL) formula according to Friedman et al [20] and Ouedraogo et al [21]. FL is the percentage of informants who claim to use certain plant species for particular healing processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fidelity level (FL) is used to calculate the relative frequency of citation (Friedman et al 1986, Ouedraogo et al 2019 The percentage of informants who claim to use specific plant species for specific healing processes is referred to as FL. This demonstrates people's preference for a certain plant species in a specific therapeutic therapy.…”
Section: Fidelity Level (Fl)mentioning
confidence: 99%